2013
DOI: 10.1007/s11095-013-1021-8
|View full text |Cite
|
Sign up to set email alerts
|

CD44 Targeting Magnetic Glyconanoparticles for Atherosclerotic Plaque Imaging

Abstract: Purpose The cell surface adhesion molecule CD44 plays important roles in the initiation and development of atherosclerotic plaques. We aim to develop nanoparticles that can selectively target CD44 for the non-invasive detection of atherosclerotic plaques by magnetic resonance imaging. Methods Magnetic glyco-nanoparticles with hyaluronan immobilized on the surface have been prepared. The binding of these nanoparticles with CD44 in vitro was evaluated by enzyme linked immunosorbent assay, flow cytometry and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 75 publications
0
39
0
1
Order By: Relevance
“…It binds specifically to the membrane receptor CD163 over-expressed by macrophages at inflammatory sites such as atherosclerotic plaques [218]. El-Dakdouki et al decorated magnetic glyconanoparticles with hyaluronan, which selectively binds to CD44 overexpressed by macrophages within vulnerable plaques [219]. As a ligand for SR-A overexpressed by activated macrophages within atherosclerotic plaques, dextran sulfate (DS) was employed by You et al to coat SPIO for imaging of atherosclerosis [220].…”
Section: Nanoparticle-based Theranostics For Dysfunctional Macrophmentioning
confidence: 99%
“…It binds specifically to the membrane receptor CD163 over-expressed by macrophages at inflammatory sites such as atherosclerotic plaques [218]. El-Dakdouki et al decorated magnetic glyconanoparticles with hyaluronan, which selectively binds to CD44 overexpressed by macrophages within vulnerable plaques [219]. As a ligand for SR-A overexpressed by activated macrophages within atherosclerotic plaques, dextran sulfate (DS) was employed by You et al to coat SPIO for imaging of atherosclerosis [220].…”
Section: Nanoparticle-based Theranostics For Dysfunctional Macrophmentioning
confidence: 99%
“…In recent years, many researches had employed HA to decorate nanocarriers for anticancer drugs to improve the targeting efficiency to solid tumors via CD44-mediated uptake, while overlooking the valuable function of HA in diagnosis and therapy of atherosclerosis [18e21]. The upregulated CD44 at atherosclerotic lesions coupled with the high affinity HA to CD44 at inflammatory sites render it attractive to utilize HA/CD44 interactions for effective plaque targeting [22,23]. Heretofore, barely any research was reported on HA-modified nanocarriers to achieve atherosclerotic lesions-targeted drug delivery.…”
Section: Introductionmentioning
confidence: 99%
“…This lack of radiosensitization was also absent in cells that were enriched for the highest expression levels of CD44 using a cell sorting approach. The HA-DESPIONs used in this study have previously been shown to be detectable in tumors and atherosclerotic plaques using static magnetic fields to provide contrast for magnetic resonance imaging [11,33]. This is because stabilized superparamagnetic iron oxide nanoparticles are characterized by inherently high T2/T2 * relaxivity causing strong local inhomogeneities which can be detected as hypointense areas.…”
Section: Discussionmentioning
confidence: 99%